Rethinking what works with offenders : probation, social context and desistance from crime - Farrall, Stephen (Abingdon, Oxon ; New York, NY : Routledge, 2021)
When it was published twenty years ago, Rethinking What Works with Offenders made a major contribution to criminological knowledge on why people stopped offending, and the impact the probation service had on the desistance process. Unlike other studies that had relied on official conviction data, it was the first to make use of self-reported data, including interviews with men and women on probation, and their supervising Probation Officers. It reconceptualised probation outcomes in terms of degrees of success rather than as 'successful' or 'unsuccessful' and offered important policy implications of these conclusions. The Twentieth Anniversary edition contains the original text along with a newForeword by Shadd Maruna and Fergus McNeill, locating the book historically and assessing its continued importance to Criminology. It also includes a new chapter by the author reporting on the key findings of the follow-up interviews in 2004 and 2010-12, reflecting on key developments in the field and developing a theory of assisted desistance. Furthermore, it features four newcommentaries from Mark Halsey, Isabelle F.-Dufour, Martine Herzog-Evans and Jos Cid reflecting on the importance and legacy of the book. This book presents an important and challenging range of findings on 'what works' in probation and with offenders and remains essential reading for anybody professionally concerned with the present and future of probation.
Probation, social context and desistance from crime: introducing the agenda -- Realism, criminal careers and complexity -- The study -- Probation, motivation and social contexts -- Defining 'success' -- The focus of probation -- Resolving obstacles: the role of probation supervision -- Motivation and probation -- Probation work: content and context -- Motivation, changing contexts and probation supervision -- Persistence and desistance -- Desistance, change and probation supervision -- The factors associated with offending -- Probation, social context and desistance from crime: developing the agenda.
Originally published: 2002.
OCLC-licensed vendor bibliographic record.
Keywords: Probation -- Great Britain; Probation -- Great Britain -- Evaluation; Recidivism -- Great Britain -- Prevention; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Penology